SOCIAL MECHANISM OF PSYCHOLOGICAL MANIPULATION IN CONTEMPORARY RUSSIAN SOCIETY - Galina I. Kolesnikova; Artem E. Astvatsaturov (Advanced Engineering Research)
On the basis of the social and philosophical discourse, the structure of the social mecha nism of psychological manipulation is revealed. The application of the mechanism in the contemporary Russian society is sp ecified.